Adelphophagy and cannibalism during early development of Crucibulum auricula (Gmelin, 1791) (Gastropoda: Calyptraeidae) from the Venezuelan Caribbean - Miloslavich, Patricia (2001)
Crucibulum auricula (Gmelin, 1791) was found living attached to rocky substrates at Isla Caribe, Estado Sucre, Venezuela between 0,5 and 1 m depth.